Co-operation and communication between the human maintenance and de novo DNA (cytosine-5) methyltransferases - Kim, Gun-Do (Oxford University Press, 2002)
Three different families of DNA (cytosine-5) methyltransferases, DNMT1, DUMT2, DNMT3a and DNMT3b, participate in establishing and maintaining genomic methylation patterns during mammalian development. These enzymes have a large N-terminal domain fused to a catalytic domain. The catalytic domain is homologous to prokaryotic (cytosine-5) methyltransferases and contains the catalytic PC dipeptide, while the N-terminus acts as a transcriptional repressor by recruiting several chromatin remodeling proteins. Here, we show that the human de novo enzymes hDNMT3a and hDNMT3b form complexes with the major maintenance enzyme hDNMT1. Antibodies against hDNMT1 pull down both the de novo enzymes. Furthermore, the N-termini of the enzymes are involved in protein–protein interactions. Immunocytochemical staining revealed mostly nuclear co-localization of the fusion proteins, with the exception of hDNMT3a, which is found either exclusively in cytoplasm or in both nucleus and cytoplasm. Pre-methylated substrate DNAs exhibited differential methylation by de novo and maintenance enzymes. In vivo co-expression of hDNMT1 and hDNMT3a or hDNMT3b leads to methylation spreading in the genome, suggesting co-operation between de novo and maintenance enzymes during DNA methylation.